High-frequency plant regeneration and histological analysis of callus in Cichorium intybus: An important medicinal plant - Dakshayini, K.; Vaman Rao, C.; Karun, Anitha; Bhavyashree, U.; Ujwal, P. (Journal of Phytology, 2016)
An efficient in vitro propagation and in vitro flowering protocols were developed for the medicinal plant Cichorium intybus (Asteraceae) using leaf disc explants. Media supplemented with the growth regulator naphthalene acetic acid (NAA) (1.5 mg/l) + 6-benzyle adenine (0.25 mg/l) was used for the initial induction of the callus and further subcultured to the same media for the proliferation of the callus. Pale yellow and green calli were noticed, which depends on incorporation of the growth hormones and their varying concentrations. Murashige and Skoog medium in addition with 2 mg/l kinetin+ 0.5 mg/l indole-3-acetic acid (IBA) + 500 mg/l casein hydrolysate resulted in maximum regeneration. Media supplemented via IBA (0.5 mg/l) and NAA (0.5 mg/l) (98%) was found to be optimum for rhizogenesis for in vitro regenerated plants. For acclimatization 5-6 weeks mature in vitro regenerated plants were transferred into the greenhouse for acclimatization. The histological study revealed the presence actively dividing meristematic cells in callus. The occurrence of the peripheral meristematic zone associated with callus was noticed in after 20 days, which formed the shoot meristems after 45 days of incubation. To our knowledge, this is the first report on high-frequency plant regeneration which was carried out indirectly from the leaf explants which was grown in controlled environment with varying concentration of the growth regulators and histology of callus of different stages from leaf explants of C. intybus.